On fishing of japanese sardine (Sardinops melanostictus) - Vasily V. Kudakaev (Известия ТИНРО)
Japanese sardine resumes mass migrations to the Russian waters since 2014 that allows to restart domestic fishery of this species. Traditionally, Russian fishermen use purse seine for the sardine landing. Capacities of both purse seine and trawl fishing of japanese sardine are analyzed. There is concluded that the trawl fishing is more appropriate for the catch processing to fish flour.